Democracy, Dictatorship and the Cultural Transmission of Political Values - Davide Ticchi; Thierry Verdier; Andrea Vindigni (Institute for the Study of Labor (IZA), 2013)
We develop a theory of endogenous regimes transitions (with a focus on democratic consolidation), which emphasizes the role of political culture and of its interaction with political institutions. Political culture reflects the extent of individual commitment across citizens to defend democracy against a potential military coup, and it is an endogenous state variable of the model along with formal political institutions. We focus on two agencies of political socialization: the family and the state. Parents invest resources in order to transmit their own political values (commitment to democracy) to their children. The state invests resources in public indoctrination infrastructures. The model displays two-way complementarities between political regimes and political culture diffusion. Consolidated democracy emerges when sufficiently many people are committed to democracy. Otherwise the model features persistent fluctuations in and out of democracy as well as cycles of political culture. Importantly, the politico-economic equilibrium may exhibit a persistent (although declining) incongruence between political institutions and political culture, which tends to evolve more slowly than formal institutions.
Keywords: P16; H11; H26; H41; 330; political culture; socialization; democracy; military; nondemocracy; political economy; political transitions; institutional consolidation; path dependency